Employee readiness for change through the lens of the cultural self-representation theory - Hechanova, Ma. Regina M. (Philippine Journal of Psychology, 2012)
Change is imperative in organizations. One fundamental tool in instigating innovation is change management. Employee engagement is seen as a primary ingredient in successfully triggering readiness to change.